Functional and biochemical subtypes of the haplotype HLA-DR3 in patients with celiac disease or idiopathic membranous nephropathy. - Sacks, S; Bushell, A; Rust, N; Karagiannis, J; Jewell, D; Ledingham, J; Wood, K; Mcmichael, A (1987)
HLA class II beta-chain polymorphism was investigated in the haplotype HLA-DR3 to determine if patients with HLA-DR3-associated diseases express normal or variant class II polymorphisms. Analysis was carried out by two-dimensional gel electrophoresis of immunoprecipitated HLA class II molecules, DNA hybridization with DR beta and DQ beta gene probes on Taq 1, Bam H1, or Rsa 1 digests, and mixed lymphocyte culture. Two subtypes of HLA-DR3 were identified in normal homozygous DR3 individuals on the basis of polymorphism in one of two DR beta chains detected, corresponding to differences in DR beta restriction fragment patterns. These polymorphisms exhibited significant linkage disequilibrium with the A1,B8,DR3 and B18,DR3 haplotypes, respectively. In proliferative experiments, cells with the B18,DR3-associated polymorphism strongly stimulated cells from donors with the B8,DR3-related polymorphism, suggesting that a T-cell epitope recognized by B8,DR3 cells lies on the B18,DR3-associated DR beta chain. In seven HLA-DR3 homozygous patients with celiac disease and three HLA-DR3-homozygous patients with idiopathic membranous nephropathy, only the normal patterns of HLA class II molecules were displayed, the B8,DR3 type occurring in all patients and the B18,DR3 type in one patient. These data suggest that celiac disease and idiopathic membranous nephropathy are not related to disease-specific HLA-DR beta or -DQ beta gene variants within the DR3 population that are revealed by these methods.